2019
DOI: 10.5812/hepatmon.91129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hepatitis B and Hepatitis C Exposure in Iranian Prisoners: A National Study in 2016

Abstract: Background: People in prisons are at high risk of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Objectives: This study aimed to evaluate the prevalence of HBV and HCV exposure and associated risk factors in Iranian prisons. Methods: This cross-sectional study was conducted in 2016, among 29 prisons in Iran, blood samples were collected using multistage sampling. HBV and HCV diagnostic tests were conducted using enzyme-linked immunosorbent assay (ELISA). Univariate and multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…In this study, 24.5% of the high risk prisoners were infected with hepatitis C, which is much higher than the infection in the general population (0.3%). 3 It is different from a study conducted in 2016 in 10 provinces of Iran including Guilan which reported 8.21% prevalence in Iranian prisoners, 9 closer to an earlier systematic review published from studies between 2004-2016 with 28% prevalence, 7 and lower than another systematic review in MENA in which Iran had 37.8% anti-HCV seroprevalence among prisoners. 4 Also, new studies have reported very diverse HCV seroprevalence rates among prisoners in the world (Table 4).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In this study, 24.5% of the high risk prisoners were infected with hepatitis C, which is much higher than the infection in the general population (0.3%). 3 It is different from a study conducted in 2016 in 10 provinces of Iran including Guilan which reported 8.21% prevalence in Iranian prisoners, 9 closer to an earlier systematic review published from studies between 2004-2016 with 28% prevalence, 7 and lower than another systematic review in MENA in which Iran had 37.8% anti-HCV seroprevalence among prisoners. 4 Also, new studies have reported very diverse HCV seroprevalence rates among prisoners in the world (Table 4).…”
Section: Discussioncontrasting
confidence: 78%
“…7 In another study conducted in 2016 among prisoners in 10 provinces of Iran, including Guilan, the prevalence of HCV antibodies was 8.21% (95% CI: 7.55-8.90). 9 These studies indicate a gradual reduction in HCV prevalence among prisoners in Iran.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, a small number of scattered studies in Iran have been conducted on highrisk groups of the community. In a study in Iran, the prevalence of HBV infection among high-risk groups, including prisoners, was 3.06% [5]. On the other hand, a systematic review study showed that the prevalence of HCV infection among prisoners was 28% [6].…”
Section: Introductionmentioning
confidence: 99%
“…The present cross-sectional study is part of a series of reiterating biobehavioral surveillance surveys (BBSSs) of HBV and HCV among Iranian prisoners that were carried out in 2015 and 2016. The methodology of BBSSs was the same in both periods and is presented in comprehensively published BBSSs (12,17), however, a summary is provided below. The statistical population included all Iranian prisoners who were in prison at the time of the study.…”
Section: Data Sourcementioning
confidence: 99%